The Effect of Service Quality And Tourism Facilities on Visitor Satisfaction of Bamboe Wanadesa Balikpapan Tourism - Enjelli, Sri Devi; Althalets, Fareis (Dinasti Publisher, 2025)
This study investigates the influence of service quality and tourism amenities on tourist satisfaction at Bamboe Wanadesa Balikpapan. A quantitative approach using an associative methodology is the research methodology employed. The population of the study was visitors to Bamboe Wanadesa Balikpapan, with a target sample of 150 respondents. Multiple linear regression and correlation analysis were employed to test the hypothesis concerning the impact of service quality and tourism amenities on visitor satisfaction. Additionally, validity and reliability assessments of the research instrument were carried out. The study's findings show that service quality and tourism amenities have a major impact on visitor satisfaction, with service quality outweighing tourism facilities. This study concludes that both factors complement each other and contribute to improving the overall tourism experience. To ensure the sustainability of tourist destinations, it is important to improve parking facilities and food courts at Bamboe Wanadesa Balikpapan Tourism, it is recommended to expand the parking area, then it is necessary to harden the land using concrete or asphalt, installing a canopy can also be an additional option to protect vehicles from direct rain, improve the quality of parking management, and develop more complete and attractive food court facilities, if realized Bamboe Wanadesa Balikpapan Tourism can provide a better experience for its visitors. In addition, by conducting periodic evaluations and involving visitors in the decision-making process, it is hoped that appropriate and sustainable solutions can be created